2011
DOI: 10.1002/stem.632
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells Reprogram Adult Cardiomyocytes Toward a Progenitor-Like State Through Partial Cell Fusion and Mitochondria Transfer

Abstract: Because stem cells are often found to improve repair tissue including heart without evidence of engraftment or differentiation, mechanisms underlying wound healing are still elusive. Several studies have reported that stem cells can fuse with cardiomyocytes either by permanent or partial cell fusion processes. However, the respective physiological impact of these two processes remains unknown in part because of the lack of knowledge of the resulting hybrid cells. To further characterize cell fusion, we cocultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
204
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(215 citation statements)
references
References 54 publications
8
204
1
2
Order By: Relevance
“…Although these data highlight the importance of MSC secretome in mediating its therapeutic effects, the potential role of other mechanisms, such as exosomes and mitochondrial transfer, should be further evaluated. 50,51 The promising therapeutic potential of MSCs is not yet fully translated into the clinic. Given the narrow window of opportunity to achieve their therapeutic effects, strategies enabling rapid delivery of "upgraded" MSCs to disease sites appear necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Although these data highlight the importance of MSC secretome in mediating its therapeutic effects, the potential role of other mechanisms, such as exosomes and mitochondrial transfer, should be further evaluated. 50,51 The promising therapeutic potential of MSCs is not yet fully translated into the clinic. Given the narrow window of opportunity to achieve their therapeutic effects, strategies enabling rapid delivery of "upgraded" MSCs to disease sites appear necessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, this view was challenged a decade ago when it was shown that membrane connections or cytoplasmic bridges form between cells in culture and that cellular organelles traverse these nanotube connections (1). Since then, considerable in vitro evidence has confirmed organelle transfer, including mitochondria, to and between tumor cells (2)(3)(4)(5)(6)(7)(8) as well as between nontumor cells (9)(10)(11)(12)(13)(14)(15). Additionally, recent phylogenetic evidence suggests that mtDNA can "move" between normal cells and tumor cells in canine venereal transmissible cancer (16,17), while pathophysiological models of lung injury (18,19), lung inflammation (19), and tumor formation by respiration-deficient tumor cells (19) have added weight to intercellular mitochondrial transfer being a new (patho) physiological phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, different types of stem cells only have the capacity to reprogram somatic cells to a certain state, which is identical to the differentiated state of this type of stem cells. As discussed above, after cell fusion, ESCs can reprogram somatic cells to pluripotent cells (Cowan et al 2005), and Yamanaka factors identified from ESCs also have the capacity to reprogram fully differentiated somatic cells to iPSCs (Takahashi & Yamanaka 2006), while human multipotent mesenchymal stem cells only have the capacity to reprogram mouse fully differentiated cardiomyocytes to a progenitor-like state (Acquistapace et al 2011), mouse totipotent zygotes could support the full-term development of mouse ESCs (Egli et al 2007). Therefore, from these points of view, the mechanism of SCNT would be different from that of stem cell-somatic cell fusion and iPSCs.…”
Section: Matured Oocytes Were Endowed With Totipotent Developmental Pmentioning
confidence: 98%